A study on the plant growth-promoting rhizobacteria (PGPR) and its efficiency to enhance the growth of MR263 variety of paddy / Khairuddin Hamid - Hamid, Khairuddin (Faculty of Plantation and Agrotechnology, 2015)
Plant growth promoting rhizobacteria (PGPR) is the bacteria that live freely in the soil rhizosphere. It is the soil bacteria that live around or at the plant roots. The mechanism of the rhizobacteria to enhance and promote the growth and development of the plant through the direct or indirect mechanism. This process can be done via discharge and production of many type of chemical into the soil rhizosphere. The use of PGPR will give the significant effect which is increase the agriculture production and quality. Other than that, the using of PGPR in agriculture will reduce the using of chemical input like pesticide, herbicide, and others which is will reduce the environmental pollution trough the agriculture activities. Thus, I was isolate the PGPR and study the characteristic of the PGPR that was took from the soil rhizosphere of paddy field 5 different location in Melaka state. The isolated PGPR that obtain from the field was randomly choose and assigned as PGPR 1, PGPR 2, PGPR 3, PGPR 4, and PGPR 5. All the five PGPR was successfully isolated and cultured in Nutrient Agar (NA) plate. In order to determine the efficiency of the PGPR isolate to enhance the growth of MR263 variety of paddy, the pot experiment was conducted and obtained. During the pot experiment, all the seeds was treated with different PGPR strain to obtain the result. Seeds that not treated was used as the control. From the pot experiment, the growth of the treated paddy seedling is better compared to the control paddy seeds. Other than that, the germination that was conducted shows the PGPR isolate was give the significant effect on increase the germination process of the seed. From the study, it can be suggested that the isolate of PGPR 1 and 4 can be used as the bio-fertilizer that can enhance the growth of paddy plant.